Ruas de estar: mobilidade e apropriação urbana - Eveline Prado Trevisan (2021)
This work refers to the relationship between mobility and urban appropriation from a discussion on the use of the street. The expression “Ruas de Estar” (Streets as Living Rooms), which gives the title to this research, symbolically unites the public (the street) and the private (the living room) in an attempt to explain a look that points beyond what would be the first function of the street: allow the movement and mobility of people. Looking at the street that welcomes and receives citizens. The street that is the setting, stage and landscape for the social expression of urban life. At the heart of the matter lies the following question: when and how can our streets, in addition to just letting pass, also be an invitation to see these public spaces as living rooms? This research starts from a specific point: the analysis of four interventions that proposed new uses for stretches of streets in different neighborhoods in Belo Horizonte, based on their effective reduction in speed limits. This investigation is anchored in two main methodologies: the investigation methods proposed by urban anthropology, in particular the “participant observation” and, considering that urban education processes definitively permeated all the work, from the field to reflection, in the methodology called “ urban pedagogy,” and which, in this research, due to the relevance it has acquired, implies a method of analysis, and also a strategy for making interventions viable. The actions of this research were directly affected by the COVID-19 Pandemic, which led to the adoption of another methodology, taking advantage of the resources of the web surveys. The research also discusses the legitimacy of the processes of appropriation of public spaces and the retaking of the streets run by the State, albeit in partnership with civil society. At the end, there is a reflection on how much of the initial questioning was possible to be answered by the research as a way to point out ways (and not replicable models) for the systematization of knowledge involving urban interventions that aim to discuss the uses of the street and the access to the city.